‘Freedom to Learn-Independent Campus’and Pre-Service Teachers Proffesional Identity Development - Lemmuela Alvita Kurniawati; Vinanda Kristianti (Graduate School of Universitas Negeri Malang, 2022)
Abstract: In response to the implementation of Merdeka Belajar (Freedom to Learn)-Kampus Merdeka (Independent Campus), this study aimed to investigate the perceived impacts of Freedom to Learn-Independent Campus (henceforth FLIC), on pre-service Teacher Professional Identity (henceforth, TPI) development. A qualitative research method by using a thematic analysis was used to analyze the data. Homogeneous online focus group discussions with three different groups of participants joining FLIC program were conducted to collect the data. There were twelve pre-service teachers who joined FLIC program involved in this study. The findings were elaborated under three themes. The themes were becoming and being didactical teachers, becoming and being pedagogical teachers, and the affordances of FLIC program for TPI development. The findings of this study offered some contributions, implications, and suggestions for further studies.Abstrak: Menyikapi pelaksanaan Merdeka Belajar-Kampus Merdeka (MBKM), penelitian ini bertujuan untuk mengetahui dampak yang dirasakan dari MBKM terhadap Identitas Profesi Guru (IPG) prajabatan. Penelitian ini menggunakan metode penelitian kualitatif dan analisis tematik untuk menganalisis data. Data didapatkan dari diskusi kelompok terarah secara daring dan bersifat homogen dengan tiga kelompok peserta yang mengikuti program MBKM. Terdapat dua belas guru prajabatan yang mengikuti program MBKM dan terlibat dalam penelitian ini. Temuan penelitian ini dijabarkan dalam tiga tema, yaitu menjadi guru didaktik, menjadi guru pedagogik, dan keterjangkauan program MBKM untuk pengembangan IPG prajabatan. Temuan penelitian ini juga menghasilkan beberapa kontribusi, implikasi, dan saran untuk studi lebih lanjut.